2020
DOI: 10.1016/j.chemgeo.2020.119794
|View full text |Cite
|
Sign up to set email alerts
|

Rare earth element and neodymium isotope tracing of sedimentary rock weathering

Abstract: Chemical weathering plays an important role in sequestering atmospheric CO 2 , but its potential influence on global climate over geological timescales remains debated. To some extent, this uncertainty arises from the difficulty in separating the respective contribution of sedimentary and crystalline silicate rocks to past weathering rates in the geological record; two types of rocks having presumably different impact on the long-term carbon cycle. In this study, we investigate the use of rare earth element (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 89 publications
(114 reference statements)
2
16
0
Order By: Relevance
“…In this study, the evidence that leached Fe-oxyhydroxide phases significantly depart from NADW-like ε Nd values clearly point towards the presence of such pre-formed continental oxides. In fact, recent investigations have shown that river-borne Fe oxides are almost systematically characterised by more radiogenic Nd isotopic compositions relative to the associated detrital material (Hindshaw et al, 2018;Bayon et al, 2020;Jang et al, 2020). This Nd isotope decoupling between paired Fe oxide and detrital silicate fractions has been attributed to the preferential erosion and/or weathering of sedimentary rocks on continents (e.g., Bayon et al, 2020).…”
Section: Core-top Evidence For a Seawater-derived Nd Isotopic Signature In Glauconitementioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the evidence that leached Fe-oxyhydroxide phases significantly depart from NADW-like ε Nd values clearly point towards the presence of such pre-formed continental oxides. In fact, recent investigations have shown that river-borne Fe oxides are almost systematically characterised by more radiogenic Nd isotopic compositions relative to the associated detrital material (Hindshaw et al, 2018;Bayon et al, 2020;Jang et al, 2020). This Nd isotope decoupling between paired Fe oxide and detrital silicate fractions has been attributed to the preferential erosion and/or weathering of sedimentary rocks on continents (e.g., Bayon et al, 2020).…”
Section: Core-top Evidence For a Seawater-derived Nd Isotopic Signature In Glauconitementioning
confidence: 99%
“…In fact, recent investigations have shown that river-borne Fe oxides are almost systematically characterised by more radiogenic Nd isotopic compositions relative to the associated detrital material (Hindshaw et al, 2018;Bayon et al, 2020;Jang et al, 2020). This Nd isotope decoupling between paired Fe oxide and detrital silicate fractions has been attributed to the preferential erosion and/or weathering of sedimentary rocks on continents (e.g., Bayon et al, 2020). For instance, recent sediments deposited near the mouth of the Amazon River display ε Nd values of −8 and −10.7 for leached Fe oxides and detrital fractions, respectively (Bayon et al, 2020).…”
Section: Core-top Evidence For a Seawater-derived Nd Isotopic Signature In Glauconitementioning
confidence: 99%
See 1 more Smart Citation
“…2). Studied samples were classified into three categories based on the lithological composition of corresponding watersheds (Table S1), following the approach described in Bayon et al (2020a): 1) Rivers draining crystalline basements dominated by igneous, metamorphic and/or siliciclastic sedimentary rocks (n=19). This category includes those rivers flowing through diverse Precambrian regions in Africa (Niger, Congo, and their tributaries, Betsiboka), northern South America (Orinoco, and its right-bank tributaries), Canada (Churchill), Australia (Murchinson, Gascoyne, Fortescue, East Alligator), Fennoscandia (Kymiijoki, Ume, Lule), and a small river from the Hercynian Armorican Massif in France (Elorn); 2) Rivers draining volcanic provinces (n=3) in Northern Ireland (River Maine, Six Mile Water) and Indonesia (Brantas); 3) Rivers draining basins of mixed lithology dominated by sedimentary rocks, which include most of the major river systems investigated in this study (n=39).…”
Section: World River Sediments and Catchment Characteristicsmentioning
confidence: 99%
“…In contrast with soil studies, which allow detailed reconstruction of weathering processes along soil depth profiles, but are also strongly affected by local effects related to differences in bedrock composition and primary mineral assemblages, the geochemical composition of fine-grained J o u r n a l P r e -p r o o f Journal Pre-proof sediments deposited near the mouth of rivers provides insights into weathering processes at the catchment scale. Such a global approach is ideally suited for investigating the mechanisms controlling the distribution of geochemical tracers in sediments and for ‗calibrating' weathering proxies against modern basin parameters (e.g., Bayon et al, 2016;Bayon et al, 2018;Bayon et al, 2020a;Bindeman et al, 2019). Two different grain-size fractions were investigated: 1) the finest clay-rich (<4µm) detrital material, which includes secondary clays formed in soils during silicate weathering processes; and 2) the silt-size (4-63µm) terrigenous component, corresponding to a mixture of both primary and weathered minerals transported in the suspended particulate load (Bindeman et al, 2019).…”
mentioning
confidence: 99%